Effects of manipulating the interstimulus interval on heat-evoked temporal summation of second pain across the age span. Issue 1 (January 2019) - Riley, Joseph L.; Cruz-Almeida, Yenisel; Staud, Roland; Fillingim, Roger B.
Abstract : Abstract: This study examined the effects of interstimulus interval (ISI) on heat-evoked temporal summation of second pain (TSSP) and tested whether greatest maintenance of TSSP would occur at longer ISIs in older adults. Several lines of evidence support that TSSP is associated with central sensitization and is centrally mediated. The participants were 198 community-dwelling adults divided into 3 age cohorts (18-39, 40-59, and 60-78 years of age). Six TSSP trials used a train of 10 contacts with a preheated probe that made repetitive contact with the volar forearm. Participants completed 2 trials at each ISI of 2.5, 3.5, and 4.5 seconds. The intraclass correlations for each pair of trials support the reliability of the current methodology. Temporal summation of second pain scores declined in a time-dependent manner across ISI. In addition, greater maintenance of TSSP at longer ISIs was observed in middle-aged and older age groups compared with the younger cohort. Significant associations were found between TSSP and measures of recent pain. Greater summation at longer ISIs in older adults would suggest slower decay of excitability in spinal neurons and infer increased risk for central sensitization with advancing age. Abstract : Temporal summation of second pain at longer interstimulus intervals among older participants suggests that slower decay of excitability in spinal neurons increases risk for central sensitization.